2022
DOI: 10.1039/d2ce00336h
|View full text |Cite
|
Sign up to set email alerts
|

Systematic arrangement control of functional organic molecules

Abstract: Functional organic molecules, especially π-conjugated molecules, have tunable functions according to their molecular design. Since their properties are significantly affected by the overlap of π-orbitals between adjacent molecules as well...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…As shown in Figure S9, the UV‐vis and emission spectra of 2,6‐ADS and each organic salt in dimethyl sulfoxide (DMSO) solution were identical, indicating that the electronic structure of 2,6‐ADS remained unchanged even in the presence of amines in the solution [14e–f] . Furthermore, the 1 H NMR spectra (Figure S10) confirmed that the interaction with amine (deprotonation of the sulfo group) had no effect on the electronic structure of the anthracene moiety [14e–f] …”
Section: Resultsmentioning
confidence: 88%
“…As shown in Figure S9, the UV‐vis and emission spectra of 2,6‐ADS and each organic salt in dimethyl sulfoxide (DMSO) solution were identical, indicating that the electronic structure of 2,6‐ADS remained unchanged even in the presence of amines in the solution [14e–f] . Furthermore, the 1 H NMR spectra (Figure S10) confirmed that the interaction with amine (deprotonation of the sulfo group) had no effect on the electronic structure of the anthracene moiety [14e–f] …”
Section: Resultsmentioning
confidence: 88%
“…The crystal structure for MeO-PTTP-MeO is reported here for the first time. The crystal structure for PTTP was previously obtained in ref for 213 K, but in this study, we present it for the room temperature (298 K). The crystallographic data for the two compounds are shown in Table S1 of the Supporting Information (SI).…”
Section: Resultsmentioning
confidence: 99%
“…Crystal engineering is the design and synthesis of molecular ordered structures based on the understanding and use of intermolecular interactions, especially hydrogen bonds and coordination bonds. [1][2][3][4][5][6] Apart from coordination bonds, the most studied nonbonding interaction in the crystal lattice is hydrogen bonding. [7][8][9][10][11][12][13][14][15] The wide exploration of hydrogen bonds has flourished owing to advances in the organic synthesis of molecules called tectonsmolecules that are designed by grafting functional groups or sticky sites by hydrogen bonds onto a central core.…”
Section: Introductionmentioning
confidence: 99%